PENGARUH KEGIATAN MENGANYAM PURUN TERHADAP KEMAMPUAN MOTORIK HALUS PADA ANAK USIA 5-6 TAHUN - Yulandari, Yulandari; Suningsih, Taruni (Bunayya, 2025)
Weaving is the process of arranging materials crosswise by inserting materials alternately to form an object. This weaving activity is useful for training motor skills, so researchers want to analyze whether there is an effect of purun weaving activities on the development of fine motor skills of children aged 5-6 years. The method used is a pre-experimental design experiment of the one shot case study type. The research sample consisted of 20 children in class B2 and used the purposive sampling technique. The data collected were carried out by observing checklist sheets and documentation. Data analysis used statistical tests with t-tests which produced a calculated t value = 5.27 and t table = 1.729. The results showed that the calculated t value was greater than the t table (5.27> 1.729), which means that (Ho) was rejected and (Ha) was accepted. In conclusion, purun weaving activities have an effect on the fine motor skills of children aged 5-6 years.